Anesthetic Management of Women With Heart Failure During Pregnancy: A Retrospective Cohort Study. Issue 3 (September 2021) - Jayasooriya, G.; Silversides, C.; Raghavan, G.; Balki, M.
Abstract : ( Int J Obstet Anesth . 2020;44:40–50) The increases in plasma volume, cardiac output, and heart rate caused by pregnancy may also lead to heart failure in women with underlying cardiac disease. Pregnancy may even reveal first-time symptoms of cardiac disease in tandem with hemodynamic stress, presenting with de novo cardiovascular conditions such as preeclampsia or peripartum cardiomyopathy. Since hypertensive disorders complicate up to 10% of pregnancies, and because known associations exist between heart failure in pregnancy and preeclampsia, this study aimed to examine management (anesthetic, medical, and obstetric) and etiologies of pregnant women with clinical heart failure presenting to a tertiary care center in Canada.